2023
DOI: 10.1038/s41467-023-36323-4
|View full text |Cite
|
Sign up to set email alerts
|

Microbiota-derived acetate enhances host antiviral response via NLRP3

Abstract: Pathogenic viral infections represent a major challenge to human health. Host immune responses to respiratory viruses are closely associated with microbiome and metabolism via the gut-lung axis. It has been known that host defense against influenza A virus (IAV) involves activation of the NLRP3 inflammasome, however, mechanisms behind the protective function of NLRP3 are not fully known. Here we show that an isolated bacterial strain, Bifidobacterium pseudolongum NjM1, enriched in the gut microbiota of Nlrp3−/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(36 citation statements)
references
References 49 publications
1
28
0
Order By: Relevance
“…These findings are within the general broader perspective of the relations of the microbiome and the rates of viral infections [ 40 , 41 , 42 , 43 ] and their severity [ 42 ]. A comprehensive review has shown that dysbiosis of the human microbiome is related to increased rates of viral infections and even suggested advanced manipulations to target gut microbiome [ 40 ]; the use of probiotics has also been suggested [ 43 ].…”
Section: Discussionmentioning
confidence: 73%
See 2 more Smart Citations
“…These findings are within the general broader perspective of the relations of the microbiome and the rates of viral infections [ 40 , 41 , 42 , 43 ] and their severity [ 42 ]. A comprehensive review has shown that dysbiosis of the human microbiome is related to increased rates of viral infections and even suggested advanced manipulations to target gut microbiome [ 40 ]; the use of probiotics has also been suggested [ 43 ].…”
Section: Discussionmentioning
confidence: 73%
“…The decisive mechanisms involved and the gut–lung axis have been explored using a mouse model. Bifidobacterium pseudolongum NjM1-enriched gut microbiota of mice protected against influenza by acetate production and inflammasome-mediated signaling of interferon production [ 41 ]. A detailed study of the oropharyngeal metabolome in pediatric patients with or without influenza A virus pneumonia demonstrated significantly higher levels of sphingolipid and propanoate metabolites between patients with influenza pneumonia and healthy controls [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…68 Bifidobacterium pseudolongum NjM1-derived acetate enhances the aggregation of mitochondrial antiviral signaling protein (MAVS) in response to receptor GPR43 (G protein-coupled receptor 43), leading to elevated IFN-I production and thus alleviating effects on virusinduced inflammation. 69 Whether it is a traditional probiotic or a new live biologic, mainstream clinical use has chosen to use probiotics after antibiotics, and there may be multiple reasons for such a combination order (Fig. 1): (1) the subsequent addition of probiotics can effectively occupy these ecological sites, thus competing to exclude the more resistant C. difficile strains, vegetative cells and spores; 9 (2) the addition of probiotics competes with the remaining C. difficile strains and their vegetative cells for nutrients essential for growth such as carbohydrates and amino acids, thus inhibiting the normal growth and metabolism of C. difficile; 19 (3) probiotics are able to secrete organic acids after colonization and affect the level of intestinal bile acid metabolism, especially enhancing the level of secondary bile acids, thus altering the intestinal growth environment to the detriment of C. difficile; 49,50 (4) after colonization, probiotics can secrete antimicrobial peptides, bacteriocins, extracellular polysaccharides and other types of antimicrobial substances, which have a direct killing effect on C. difficile strains; 64,[70][71][72] (5) probiotics can activate the intestinal immune system and enhance the related immune response to clear C. difficile; 73 and (6) probiotics can indirectly promote the growth of low-abundance beneficial microbes in the gut by "cross-feeding", thus co-antagonizing C. difficile.…”
Section: Mode Of Action Of Probiotics In the Gutmentioning
confidence: 99%
“…68 Bifidobacterium pseudolongum NjM1-derived acetate enhances the aggregation of mitochondrial antiviral signaling protein (MAVS) in response to receptor GPR43 (G protein-coupled receptor 43), leading to elevated IFN-I production and thus alleviating effects on virus-induced inflammation. 69…”
Section: Order Of Priority In the Combination Of Bacteria And Drugmentioning
confidence: 99%